Egg Quality during the Pubertal Transition—Is Youth All It’s Cracked Up to Be? - Duncan, Francesca E. (Frontiers in Endocrinology, 2017)
Although it is well-accepted that egg quality decreases with advanced maternal age, we do not know how it is affected at the earliest ages during the pubertal transition – likely because this young population is not typically reproducing. However, in the setting of fertility preservation more childhood cancer patients are surviving their diagnosis due to medical advances, forcing patients and their families to consider their future fertility at a very young age. Ex vivo in vitro maturation (IVM), in which cumulus oocyte complexes harvested from ovarian tissue are cultured to obtained mature gametes, is gaining traction as a fertility preservation method that is coupled to ovarian tissue cryopreservation. This method is particularly suitable for prepubertal and young adolescent girls, although live births have not yet been reported in gametes derived from females during the pubertal transition. Importantly, the period immediately following menarche in primate species (nonhuman primate and human) is characterized by relative subfecundity or sterility, and data from agricultural species and humans suggest that this may in part be due to increased chromosomal abnormalities in the egg. Together this data provides a compelling rationale for pushing the age boundary of when egg quality is considered, for performing further basic research to understand egg quality during this period, and for appropriately counseling patients.